AB0495 Audiovestibular involvement in systemic sclerosis: our exprerince. (23rd January 2014) - Lanciano, E.; Rotondo, C.; Praino, E.; Covelli, M.; Iannone, F.; Lapadula, G.
Abstract : Background: Hearing and balance disorders may occur in systemic sclerosis (SSc) as a result of the immune-mediated inner ear damage, the etiology being vasculitis and fibrosis. Objective of our study was to evaluate the prevalence of the audiovestibular organ involvement and its relationship with duration of the disease in patients with SSc. Methods: In order to evaluate the nature and association of audiovestibular disturbances and systemic sclerosis (SSC), 19 selected SSc patients (2 males and 18 females) were studied with a detailed audiological and vestibular examination. Patients were 15-77 years old and were affected by SSc from around10 years. Patients had no history of exposure to noise, ototoxic drugs, hearing loss metabolic desease-associated and genetic hearing loss. Otoscopy, liminal tonal audiometry, speech audiometry, impedance and evoked otoacoustic emissions was performed. Results: Nine patients (47%) had normal hearing (PTA < 20 dB HL), while ten patients (53%) had hearing loss (one had severe hearing loss with PTA ≤ 71-90 dB HL, five moderate PTA ≤ 41-70 dB HL and four mild heraring loss with PTA ≤ 20- 40dB HL). Four patients had unilateral and 15 bilateral hearing loss. Nine patients (47%) showed sensorineural hearing loss mostly bilateral and symmetrical, while four patients (21%) had a bilateral transmissive hearing loss and six patients (32%) had normal hearing. Conclusions: We observed a loss of hearing threshold sensorineural, bilateral and symmetrical, higher in subjects aged 55-64 years with 9-10 years disease duration. SSC appears to be directly responsible for audiovestibular damage, no other apparent cause could be revealed. Thus, screening for audiovestibular involvement should be considered in SSc patient follow-up. References: Audiovestibular involvemente in Systemic Sclerosis. Berrettini S, Ferri C, Pitaro N, Bruschini P, Latorraca A, Sellari-Franceschini S, Segnini G. ORL J Otorhinolaryngol Relat Spec. 1994 Jul-Aug;56(4):195-8. Vestibular system in patients with systemic sclerosis. 2011 May-Jun;65(3):202-7. doi: 10.1016/S0030-6657(11)70676-X. Polish. Audiovestibular manifestations in patients with limited systemic sclerosis and centromere protein-B (CENP-B) antibodies. Amor-Dorado JC, Arias-Nuñez MC, Miranda-Filloy JA, Gonzalez-Juanatey C, Llorca J, Gonzalez-Gay MA. Medicine (Baltimore). 2008 May;87(3):131-41. Disclosure of Interest: None Declared